A very rare localization of a rare disease: palmar lichen nitidus - İrem Nur Durusu; Dilara Güler; Gülhan Gürel; Gülsüm ¸eymaS Yalçın (Sociedade Brasileira de Dermatologia, 2022)
Abstract Lichen nitidus is an uncommon lichenoid dermatosis that could be defined as multiple, separated, shiny, pinpoint, pale to skin-colored papules. Palmoplantar lichen nitidus is a quite rare variant of lichen nitidus. It is hard to make a diagnosis of palmar lichen nitidus when there are no lesions elsewhere on the body. There are some dermoscopic features defined for both palmoplantar and non-palmoplantar lichen nitidus that might be useful to facilitate the diagnosis before histopathological examination. Herein, we report a case of a 24-year-old man diagnosed with isolated palmar lichen nitidus with dermoscopic features and histopathological confirmation.